Prolactin and Lactation as Modifiers of Diabetes Risk in Gestational Diabetes - Ramos-Román, M. A. (Hormone and Metabolic Research, 2011)
Pregnancy and puerperium are periods of intense hormonal changes. Maternal metabolism adapts to spare the mother from harm on behalf of her developing offspring and major alterations maintain normal glucose tolerance. Insulin secretion increases during a normal pregnancy to compensate for pregnancy-induced insulin resistance and maintain euglycemia. Women at risk for gestational diabetes have insulin resistance before conception. Gestational diabetes develops when a woman at risk is unable to meet the insulin secretory demands imposed by the additional insulin resistance characteristic of pregnancy. The lactogens, human placental lactogen and prolactin, are major stimuli for the adaptation of the endocrine pancreas during gestation. This review discusses the role of lactogens on glucose homeostasis during pregnancy and proposes a mechanism by which the hormonal control of lactation, led by prolactin, may regulate adipocyte biology, glucose and lipid metabolism, and guard postpartum women against type 2 diabetes.
Keywords: breastfeeding; hyperprolactinemia; pregnancy; puerperium